Is Learning Trajectory Necessary for Mathematics Junior High School Students’ Understanding Ability? - Pramesti, Getut; Surjatiningsih , Mahanani; Nastiti, Bela Talita Yuli (Universitas Negeri Semarang, 2024)
A learning trajectory (LT) is needed to help teachers prepare materials, methods, and strategies to achieve learning objectives, activities, and student expectations. Hence, the purpose of this study is to determine the necessity of the LT by providing evidence of the significance of learning trajectory in improving mathematics junior high school students' conceptual understanding abilities. This quantitative research used descriptive analysis and inference by using univariate and multivariate statistical analysis. The population in this study were eighth-grade students of Public Junior high school in Surakarta Indonesia. We chose 32 students as a sample subjected to the LT class, whereas 31 were subjected to the non-LT class. We analyze the mathematics concept student’s understanding ability and its components. With a confidence level of 95%, the results showed that the mathematics concept of junior high school student's understanding ability in LT classes was better than students' understanding of concepts in non-LT classes. The unique findings of this research are that students' understanding abilities in restating a concept and classifying objects according to certain properties of the concept are the same for both LT and non-LT classes. In non-LT classes, students' ability to develop necessary or sufficient conditions for a concept is better than in LT classes. Meanwhile, the understanding abilities of LT classes that are better than those in non-LT classes include giving examples and non-examples of a concept, presenting concepts in the form of mathematical representations, using and utilizing and selecting certain operating procedures, and applying concepts or algorithms to solutions.